Age and Tissue Specific Differences in the Development of Acute Insulin Resistance Following Injury - Zhai, Lidong (2009)
Injuries, hemorrhage, sepsis, burn, and critical illnesses all induce insulin resistance, and insulin resistance is strongly associated with advancing age. However, the effect of age on injury-induced insulin resistance is not well studied. We performed surgical trauma in male rats of three different ages (3-, 6- and 10-weeks old). Rats were either hemorrhaged to a mean arterial pressure of 35–40 mmHg and subsequently maintained at that pressure for up to 90 minutes, or maintained without hemorrhage as controls. Results indicate that insulin-induced intracellular signaling was diminished in liver and skeletal muscle of 6- and 10-week old rats following trauma and hemorrhage. In even younger rats, immediately post-weaning (approximately 3 weeks of age), insulin signaling was lost in liver, but not in skeletal muscle. Glucocorticoids can play a role in the chronic development of insulin resistance. Our results demonstrate that corticosterone levels were increased in 6- and 10-week old animals following hemorrhage, but little change was measured in 3-week old animals. Blockade of glucocorticoid synthesis prevented the development of insulin resistance in skeletal muscle, but not in liver of 6-and 10-week old rats. Moreover, skeletal muscle glucocorticoid receptor levels increased dramatically between 3 and 6 weeks of age. These results indicate that trauma and hemorrhage-induced hepatic insulin resistance occurs at all ages tested. However, there is no development of insulin resistance following trauma and hemorrhage in skeletal muscle of post-weaning rats. In skeletal muscle of 6- and 10-week old rats, inhibition of glucocorticoid levels prevents the development of insulin resistance.